Optimizing network of the VDI server using multi NICs with software defined networking (SDN) / Muhammad Fendi Osman - Osman, Muhammad Fendi (2015)
The demand of the Bring Your Own Device (BYOD) has been increasing from day to day since the use of the mobile devices became popular on 2010. Nowadays, many organizations already support BYOD and some of organization considering to supporting it because BYOD have many advantages such as increasing employees’ productivity and able to reduce organization cost. In BYOD environment, employees using their mobile devices accessing to their virtual corporate desktop via network to the centralized Visual Desktop Infrastructure (VDI) server. It can be concluded that VDI is the key enabler for the BYOD that created multi number of virtual desktop hosted on the remote server for user or employees to access. Handling multi connection and many clients accessing to the centralized VDI server may cause of latency and delay because of limited of bandwidth. To provide a greater bandwidth, uninterrupted service and best user experiment, server can optimize and improve the connectivity between server and network switch by leverage multi Network Interface Card (NICs) that has been installed on that server. Several approaches can be considered in this scenario and this paper will apply Software Defined Networking (SDN). The OpenFlow-based SDN is able to provide a greater bandwidth and do traffic prioritization and dynamic path-selection in multi path environment. One (1) program will be developed to instruct the OpenFlow-based SDN Controller for route modification. The evaluation of the SDN approach will be conducted by comparative study between legacy network technology and other approach such as NIC Bonding. After all have been tested, result from the comparative study shows that SDN and its features are able to optimize network of the VDI server.